O (in)divíduo compulsivo: uma genealogia na fronteira entre a disciplina e o controle - Siqueira, Leandro Alberto de Paiva (2009)
Beginning in the 1990s, diverse habits, conducts, and daily-life behaviors, when practised in excess, in an uncontrolled or repetitive manner began to be biologized by psychiatry and progressively included in diagnostic manuals of mental disorders. Generically known by the term compulsions, these "new mental disorders" group together thoughts and desires that provoke discomfort, fear, and anxiety the activities whose engagement brings pleasure such as playing, eating, buying, doing physical exercise, working, sex, surfing the internet, using substances that alter perception, relationships, and religion. The emergency of compulsions as a new "epidemic" to be combatted against occurred at the same that psychiatry went through a reformulating process of its practices and knowledge thanks to new computo-informational technologies, the development of modern psychopharmaceuticals, and the incorporation of the contents regarding the mental and human behavior produced by the neurosciences. This research aims to trace a genealogy of compulsions in order to problematize dispositifs of power that operate subjects at the moment when disciplinary societies, analyzed by Michel Foucault, come to be overlapped by control societies, as pointed out by Gilles Deleuze. In this change, the asylum no longer is the principal economy of power in the formatation of subjectivities, in order to be substituted by technologies that operate in open air and result in normalizations of the normal. They are technologies that combine subjections and machinic servitudes, promoting processes of (in)dividuation, and take place on an environment by means of flows of mental health that convokes the policing of "disfunctions", the auto-vigilance of behaviors and conducts, and the formation of organized groupings of carriers of disorders. Understood as unfoldings of neoliberal governamentality, compulsions are configured as one more dispositif of an "era of moderation and moderates" and of the proliferation of the sensations of liberty